The Rise of Mass Prestige : How Affordable Luxury Brands Influence Customer Identity - Zacharczuk, Julia (2025)
The thesis explores the phenomenon of mass prestige - the rise of affordable luxury brands and its influence of customer identity. As luxury-like products become increasingly accessible, the thesis aims to understand underlying factors influencing the popularity of such brands and how they reshape social behaviour and customer identity. The thesis analysis economic and psychological drivers behind the growing appeal of affordable luxury. Furthermore, the shifting customer expectations towards mass prestige brands in the contemporary market are explored. The core focus is placed on the aspiration, perceived status and purchasing behaviour within the segment of the market, achieved by mixed-method approach. Through qualitative and quantitative analyses, the thesis underscores to understand how customers use affordable luxury as a mean of self-differentiation and to align with aspirational social groups.